1994
DOI: 10.1159/000188227
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathological Changes Induced by Cadmium-Exposure in Canine Proximal Tubular Cells: A Cytochemical and Ultrastructural Study

Abstract: A highly sensitive cytochemical method for demonstrating intracellular Cd using 8-hydroxyquinoline was developed and applied in the cytopathoiogicai study of primary-cultured renal tubular cells from beagle kidneys. The Cd-8-hydroxyquinoline emitted a yellowish-green fluorescence which first appeared in the cytoplasm within 30 min and in the nucleus about 60-90 min after exposure to 100 mM CdCl2. It was noteworthy that intranuclear Cd was stained in the nucleolar regions. The sensitivity of the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…Although our findings provide no direct insight regarding the mechanism of cadmium induction of germ cell apoptosis, Betka and Callard (1999) have found that, although cytosolic cadmium-binding components other than heavy-metal-binding metallothionein can, to some extent, account for the cadmium accumulation gradient in the shark testis, a second nuclear-associated component of cadmium is present in larger amounts in immature than in mature spermatogonial regions in the testis of Squalus. Cadmium has a high affinity for nucleic acids and accumulates within the nuclear compartment, even when present in trace amounts (Snow 1992;Hamada et al 1994). Nuclear-associated cadmium may displace zinc in polymerases, other metalloenzymes or transcription factors, all of which are present in larger amounts in the nuclei of proliferating cells (Din and Frazier 1985) or it may directly induce chromatin changes (Banfalvi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings provide no direct insight regarding the mechanism of cadmium induction of germ cell apoptosis, Betka and Callard (1999) have found that, although cytosolic cadmium-binding components other than heavy-metal-binding metallothionein can, to some extent, account for the cadmium accumulation gradient in the shark testis, a second nuclear-associated component of cadmium is present in larger amounts in immature than in mature spermatogonial regions in the testis of Squalus. Cadmium has a high affinity for nucleic acids and accumulates within the nuclear compartment, even when present in trace amounts (Snow 1992;Hamada et al 1994). Nuclear-associated cadmium may displace zinc in polymerases, other metalloenzymes or transcription factors, all of which are present in larger amounts in the nuclei of proliferating cells (Din and Frazier 1985) or it may directly induce chromatin changes (Banfalvi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium may lead to interstitial fibrosis and apoptosis in proximal tubule cells following tubular cell necrosis and inflammation [49,50] . In the kidney, cytosolic cadmium gives rise to the formation of free oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…5). Cadmium can induce apoptosis in isolated T lymphocytes (11) and cultured LLC-PK1 cells (31) and lead to apoptotic cell damage in canine proximal tubules (17) and rat testicular tissue (56). Most observations of Cd 2ϩ -mediated cell death are consistent with the caspase-dependent intrinsic pathway of apoptosis.…”
mentioning
confidence: 84%